Topographic anatomy of the heart of adult mithun and yak - SARMA, M; KALITA, S N; BHAITACHARYA, M; SARMA, K K (The Indian Journal of Animal Sciences, 2014)
The topographic anatomy of the heart of 3 adult mithuns and yaks was investigated by gross dissections. The heart of mithun and yak was lodged in the middle mediastinal space. The base exterided from the caudal border of the third rib to the cranial border of the sixth rib in mithun, which in yak extended from the caudal border of third rib to the middle of fifth intercostal space. The apex was at the level of fifth chondrosetemal articulation in mithun, whereas it was at sixth in yak. The slit like right cardiac notch in yak was a peculiarity.